Ethical and legal considerations of mood enhancement technology - Kamenjasevic, Erik (Frontiers in Human Dynamics, 2024)
Technology qualifying as human mood enhancement can be developed, on the one hand, for the wellbeing and mental health of their users (therapy) and, on the other hand, for changing the mood of their users above levels of normality (enhancement). Such technology provokes debates concerning its societal, ethical and legal consequences for individuals and society as a whole. This paper's aim is twofold. It first aims to show an overview of the often-occurring arguments in the ethics debate about mood enhancement technology and outline which arguments should be considered relevant for supporting the legislative debate. The second aim of the paper is to highlight some of the main legal aspects concerning this technology through the human rights lens of the United Nations, the Council of Europe, and the European Union.